Restructuring and functional heads - Cinque, Guglielmo (Oxford ; New York : Oxford University Press, 2006)
Collects the articles of Guglielmo Cinque of the University of Venice. This book is divided into two sections, the first on restructuring, a central topic in Romance syntax and with connections to other language groups as well. The second part focuses on the consequences of treating clausal functional heads as members of a universal hierarchy.
Introduction; 1. "Restructuring" and Functional Structure; 2. The Interaction of Passive, Causative, and "Restructuring" in Romance; 3. "Restructuring" and the Order of Aspectual and Root Modal Heads; 4. A Note on "Restructuring" and Quantifier Climbing in French; 5. Issues in Adverbial Syntax; 6. Complement and Adverbial PPs: Implications for Clause Structure; 7. The Status of "Mobile" Suffixes; 8. A Note on Mood, Modality, Tense, and Aspect Affixes in Turkish; References; Language Index; Name Index; Subject Index
Includes bibliographical references (pages 187-208) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Grammar, Comparative and general -- Syntax; Romance languages -- Syntax; Syntaxe; Langues romanes -- Syntaxe; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Syntax; Grammar, Comparative and general -- Syntax; Romance languages -- Syntax; Wortstellung; Bewegung; Minimalist program; Funktionale Kategorie; Hoofd (taalkunde); Werkwoorden; Grammaticale functie; Syntaxis; Sintaxe; Gramática comparada; Lingüística indo-européia.